Filosofia em atos e as contribuições da teoria crítica para a fundamentação de um currículo emancipatório - Nascimento, Mauro Antônio do (Universidade Federal de São Carlos, 2019)
This thesis is aimed at understanding the determinations that structure school curricula and the contributions of Critical Theory to the development of an emancipatory education. Throughout this research, a proposal was identified to create a Historical-psychoanalytic Philosophy with the perspective to support the conception of emancipation, being the object of this study. Based on the foundations of Critical Theory, Marx and Freud, it was possible to understand the multiple determinations that condition the individual and investigate the causes of man's regression to barbarism. Through the proximity between historical-dialectic materialism and psychoanalysis, driven by the Frankfurtians, the theoretical field ‒ of intervention ‒ of the philosophy of praxis was expanded, specifically with the analysis of the tensional relationship of the drives governed by the principle of pleasure, confronted by the principle of reality that were brought to the scene of the educational debate. These investigations, supra and intra-individual, in regard to the human condition, completed Marxism and enabled the Freudian aspiration to create a science capable of understanding the psycho-political symptoms, whose causes propagate psychopathological states and imprison a growing number of individuals in the domains of Thanatos. According to the present scenario and with the aim of promoting an emancipatory education, the Philosophy in Acts Project is presented in this research as a proposal for an educational product. The implication of this proposal is to understand that art, as a product of imagination and drives, allows man to fantasize and to be free.
Philosophy in acts and the contributions of critical theory to the foundation of an emancipatory curriculum
Keywords: Teoria crítica; Psicanálise; Filosofia histórico-psicanalítica.; Educação; Currículo; Arte; Emancipação; Critical theory; Psychoanalysis; Historical-psychoanalytic philosophy.; Education; Curriculum; Art; Emancipation; LINGUISTICA, LETRAS E ARTES::ARTES::FUNDAMENTOS E CRITICA DAS ARTES; LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO; CIENCIAS HUMANAS::FILOSOFIA; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::FILOSOFIA DA EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL; LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO::DRAMATURGIA